2015
DOI: 10.1111/geb.12305
|View full text |Cite
|
Sign up to set email alerts
|

Resistance and resilience of terrestrial birds in drying climates: do floodplains provide drought refugia?

Abstract: Aim Climate refugia will become increasingly important for biota as climate change causes an increased frequency and intensity of extreme events, such as drought. Floodplains are potential drought refugia because they have cooler and more mesic microclimates than adjacent areas, and greater water availability through shallower groundwater and flooding. We explored the role of floodplains as drought refugia by estimating the resistance and resilience of terrestrial birds over a 13‐year drought (the ‘Big Dry’) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 39 publications
2
49
0
Order By: Relevance
“…Such factors might explain variation in resistance and resilience among otherwise ecologically similar units (i.e., ecological units with similar intrinsic attributes). For example, during a severe drought in south-eastern Australia, Selwood et al [44] and Haslem et al [45] showed that the resistance of bird communities to drought was affected by environmental variables (vegetation type and the extent of tree cover, respectively). These findings suggest that extrinsic factors amenable to conservation management (either through habitat restoration or protection) modulate resistance and resilience.…”
Section: Trends In Ecology and Evolutionmentioning
confidence: 99%
See 3 more Smart Citations
“…Such factors might explain variation in resistance and resilience among otherwise ecologically similar units (i.e., ecological units with similar intrinsic attributes). For example, during a severe drought in south-eastern Australia, Selwood et al [44] and Haslem et al [45] showed that the resistance of bird communities to drought was affected by environmental variables (vegetation type and the extent of tree cover, respectively). These findings suggest that extrinsic factors amenable to conservation management (either through habitat restoration or protection) modulate resistance and resilience.…”
Section: Trends In Ecology and Evolutionmentioning
confidence: 99%
“…For instance, the 'climate refuge' concept is linked to both resistance and resilience [44]. Microclimates that are buffered from climatic extremes allow individuals to survive, or allow continued recruitment at the local scale, such that such locations have higher resistance to drought.…”
Section: Rtmentioning
confidence: 99%
See 2 more Smart Citations
“…Drought can impact birds by reducing breeding success (Colón, Long, & Morrison, 2017;Cruz-McDonnell & Wolf, 2016;Skagen & Adams, 2012), causing abundance shifts (Albright, Pidgeon, Rittenhouse, Clayton, Wardlow, et al, 2010;Gorzo et al, 2016;Selwood, Thomson, Clarke, McGeoch, & Mac Nally, 2015), reducing species richness , or by driving interannual range shifts or dispersive movements (Bateman et al, 2015). Drought can impact birds by reducing breeding success (Colón, Long, & Morrison, 2017;Cruz-McDonnell & Wolf, 2016;Skagen & Adams, 2012), causing abundance shifts (Albright, Pidgeon, Rittenhouse, Clayton, Wardlow, et al, 2010;Gorzo et al, 2016;Selwood, Thomson, Clarke, McGeoch, & Mac Nally, 2015), reducing species richness , or by driving interannual range shifts or dispersive movements (Bateman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%